Chemiluminescence from the Reaction of Iodine with Active Nitrogen - Tang, Xiao-Shuan; Cheng, Yuankui; Wang, Hong-Mei; Chu, Yan-Nan (Asian Journal of Chemistry, 2011)
Active nitrogen has been prepared by hollow-cathode discharge of high pure nitrogen gas in a flow reactor. The emission spectra from the reaction of iodine with active nitrogen are studied. The strong emission spectra of NI(b1Σ+ → X3Σ–) in the range of 620-800 nm have been observed when iodine vapours carried by nitrogen gas were introduced into a stream of active nitrogen. This is the first experimental evidence for the generation of excited state of NI(b1Σ+) via the chemical reactions of iodine with active nitrogen. The results show that vibrationally unrelaxed emission spectra from the electronically excited state NI(b1Σ+) are observed and the production NI(b1Σ+) is formed directly by the reaction of excited nitrogen atom N(2P) with I2.